Influence of 4-week lower extremity high-intensity interval training on energy metabolism and maximal oxygen uptake of elite swimmers - Rangxi Jin; Junhui Sun; Na Jiang; Chao Chen (PeerJ, 2025)
Objectives This study examines the effects of a 4-week high-intensity interval training (HIIT) program on energy metabolism and maximal oxygen uptake (VO2max) in elite swimmers, aiming to provide empirical evidence for optimizing competitive swimming training. Methods Twenty-four competitive swimmers were randomly assigned to either an HIIT experimental group or a control group. The experimental group underwent a structured 4-week lower-limb HIIT program, while the control group continued their regular training regimen. Energy metabolism parameters and VO2max were assessed using a Lode lower-limb power cycle and a gas metabolism analyzer. Repeated measures analysis was used to examine interaction effects, with data analysis conducted at a significance level of P < 0.05. Results The HIIT group exhibited significant improvements in all energy metabolism parameters and VO2max. Phosphagen energy supply increased from 40.39 ± 9.46 kJ to 58.27 ± 9.12 kJ (P < 0.001), glycolytic energy supply increased from 41.81 ± 9.81 kJ to 59.06 ± 10.86 kJ (P < 0.001), and aerobic energy supply increased from 132.29 ± 25.12 kJ to 173.32 ± 29.50 kJ (P < 0.001). Consequently, total energy supply rose from 214.48 ± 38.58 kJ to 290.65 ± 42.01 kJ (P < 0.001). Additionally, VO2max significantly improved from 51.48 ± 3.85 ml/min/kg to 55.03 ± 4.90 ml/min/kg (P = 0.041), whereas no significant changes were observed in the control group. Conclusion The findings confirm that a 4-week lower-limb HIIT program significantly enhances energy metabolism and VO2max in elite swimmers. These results underscore the efficacy of HIIT in improving metabolic adaptability, thereby supporting its application as a key training strategy for optimizing competitive swimming performance.